Scattering Parameters prediction for 433MHz SAWR with Minimum Insertion loss - M. M. Elsherbini; M. F. Elkordy; A. M. Gomaa (Institute of Advanced Engineering and Science, 2016)
A proposed schematic design for surface acoustic wave resonator (SAWR) is introduced in this paper. A simplified equivalent model for both one and two port 433MHz SAWR is built. Scattering parameters of the proposed design is extracted and compared with a commercial one of the same resonant frequency. Advanced system design tool is nominated to give the main parameters like Impedance and Admittance with their real and imaginary response. The insertion loss predicted mathematically and recorded from simulation then compared with the measured value. The proposed design tool introduced adequate results with minimum hardware procedure specifications.